Komodifikasi Berita Dibalik Ideologi Ekonomi Politik Media (Studi Pada Program ‘Polemik‘ Di Radio Sindo Trijaya 104.6 Fm Jakarta) - Dyah Rachmawati Sugiyanto (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2015)
AbstractThrough the media political economy approach, this study reveals how the commodification taken place on a media company that produced actual information in a program. The results showed that the commodification of news on talk show program of Polemik Sindo Trijaya runs behind the ideology of the political economy of media. In the commodification of the concentration of media content is known that more frequent lifting polemic political topic. Politic is considered the most attractive political issue than the issue of cultural, economic, and health. The commodification in the public discussion of the concentration, it is known that the Polemik is aimed at educating the public (listener) to act on the knowledge that they had heard. This indicates that the editorial team cares with the audience, not as disclosed Mosco that commodification is not overly concerned with the audience. In the commodification of the concentration of workers, shown that the editorial team works together to support the ideals of the concept of a talkshow program, find the right sourceperson, while the editors are behind the ideology of the political economy of the media itself.Abstrak Melalui pendekatan ekonomi politik media, penelitian ini mengungkap bagaimana komodifikasi berlangsung pada sebuah perusahaan media yang mengemas informasi aktual dalam sebuah program. Hasil penelitian menunjukkan bahwa komodifikasi berita dalam program talkshow Polemik Sindo Trijaya berlangsung di balik ideology ekonomi politik media. Dalam komodifikasi dalam konsentrasi isi media diketahui bahwa Polemik lebih sering mengangkat topic politik. Politik dianggap isu paling menarik dibandingkan isu kebudayaan, ekonomi, dan kesehatan. Komodifikasi dalam konsentrasi pembahasan mengenai khalayak, diketahui bahwa Polemik bertujuan mendidik publik (pendengar) untuk bersikap atas pengetahuan yang telah didengarnya. Hal ini menunjukkan bahwa Tim redaksi masih peduli dengan khalayak, tidak seperti yang diungkapkan Mosco bahwa komodifikasi tidak terlalu konsen dengan khalayak. Komodifikasi pada konsentrasi pekerja, diketahui bahwa tim redaksi bekerja sama mendukung idealisme konsep program talkshow, selektif memilih dan mengundang narasumber demi menjaga kekhasan talkshow, yang sebenarnya mereka berada dibalik ideology ekonomi politik media itu sendiri.